RENAL LYMPHANGIECTASIA- AN UNUSUAL MIMICKER OF RENAL HYDRONEPHROSIS - Tashkova, Zorica; Arifi, Njomza; Stojovska Jovanovska, Elizabeta; Aliji, Vjolca; Markovik, Snezhana (Journal of Morphological Sciences, 2021)
Renal lymphangiectasia is a rare malformation of the renal lymphatics. It occurs in both children and adults and can be unilateral or bilateral with no gender predilection. It is a condition characterized by different degrees of dilatation of the lymphatic ducts.  Because of the rarity, it can be easily misdiagnosed for other cystic masses, most commonly peripelvic cysts, renal cysts or hydronephrosis. Usually is asymptomatic and incidental finding, but in severe cases can lead to hypertension and renal failure. We report a case of unilateral renal lymphangiectasia in adult male patient with medical history of hydronephrosis and characteristic radiologic CT findings. From imaging methods, we conducted ultrasound (US), contrast enhanced computed tomography (CT) and CT angiography, because they have an important role as diagnostic procedures to recognize renal lymphangiectasia. Kidney cystic lesions revealed on ultrasound and confirmed on CT as hypodense intrarenal multiloculated findings, as well as fluid attenuation collections, not always go in favor of hydronephrosis. Knowledge of the radiological findings associated with renal lymphangiectasia can contribute to better differentiation from other conditions and with the right diagnosis, successful management and treatment can be provided for the patient. Keywords : renal lymphangiectasia, hydronephrosis, computer tomography. https://doi.org/10.55302/JMS2143166t